2020
DOI: 10.1007/s00168-020-01025-y
|View full text |Cite
|
Sign up to set email alerts
|

China’s regional public safety efficiency: a data envelopment analysis approach

Abstract: This study develops a comprehensive public safety efficiency index that includes the inputs and outputs of regional public safety. The DEA-BC 2 model was used to measure the technical efficiency (TE), pure technical efficiency (PTE), and scale efficiency (SE) of public safety at 31 province-level administrative divisions (regions) in China from 2014 to 2018, and to analyze the effectiveness of public safety in each year. The findings indicate that the average TE, PTE, and SE of all regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The study indicated that companies with appropriate OHS facilities tend to be more inclined towards innovation thus stressed on appropriate measures from both practitioners and governments. Zou et al (2020) developed a comprehensive index for public safety incorporating outputs and inputs of the respective factor for the regions of China. The authors used the index to measure different efficiencies through DEA procedure for the period of 2014-2018.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study indicated that companies with appropriate OHS facilities tend to be more inclined towards innovation thus stressed on appropriate measures from both practitioners and governments. Zou et al (2020) developed a comprehensive index for public safety incorporating outputs and inputs of the respective factor for the regions of China. The authors used the index to measure different efficiencies through DEA procedure for the period of 2014-2018.…”
Section: Literature Reviewmentioning
confidence: 99%